Religion, personality, and clinical assessment - Burnett, David W. (Journal of religion and health, 1979)
Religion is an integral part of every person's life and occupies a central place in every personality. Viewing "religion" as referring to that which is of primary importance in one's life, one sees it as performing an integrative function, consolidating and ordering all of the "inputs" to personality, and giving consistency to one's behavior. Thus, an understanding of the individual and an assessment of his religion are necessary for a complete understanding of his problems.